2022
DOI: 10.1002/fsn3.2989
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus johnsonii 6084 alleviated sepsis‐induced organ injury by modulating gut microbiota

Abstract: Sepsis is a public cause of death in intensive care unit patients. Probiotics were widely used to increase the survival rate of sepsis by a series of clinical research. The purpose of this research was to investigate the therapeutic effects of Lactobacillus johnsonii 6084 in septic mice. Sepsis mouse model was induced by LPS treatment. The influence of L. johnsonii 6084 on the protection of organ injury induced by sepsis was explored. Moreover, the composition of gut microbiota was studied to clarify the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies reported that the administration of these Lactobacilli could facilitate the reconstruction of a balanced microbiota with improved intestinal integrity in mice. [17][18][19] Introducing a probiotic mixture containing six Bifidobacteria and Lactobacillus strains to postsurgery patients also lead to a significant reduction in pro-inflammatory cytokines and restoration in the intestinal microenvironment. 20 Hence, these findings indicated that HkyuLL 10 suppresses CRC tumourigenesis, at least in part, through modulating and renovating the gut microbiota back to healthy and balanced conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the administration of these Lactobacilli could facilitate the reconstruction of a balanced microbiota with improved intestinal integrity in mice. [17][18][19] Introducing a probiotic mixture containing six Bifidobacteria and Lactobacillus strains to postsurgery patients also lead to a significant reduction in pro-inflammatory cytokines and restoration in the intestinal microenvironment. 20 Hence, these findings indicated that HkyuLL 10 suppresses CRC tumourigenesis, at least in part, through modulating and renovating the gut microbiota back to healthy and balanced conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus johnsonii and Weissella jogaeotgali are two important probiotics that produce acid, inhibit bacteria and have good adhesion to intestinal epithelial cells. It performs well in improving the structure of the gut microbiota and enhancing the integrity of the intestinal barrier ( Teixeira et al., 2021 ; Bai et al., 2022 ; Han et al., 2022 ; Fanelli et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…30,32 The Bacteroidota, also known as Bacteroidetes, is an anaerobic bacterium that plays a role in immunity and 33 It is usually associated with gut inflammation, and its abundance is also different before and after the treatment of sepsis. 34,35 In the Circos diagram, Firmicutes and Bacteroidota is a dominant species at the phylum level. Moreover, the abundance of Firmicutes in the sepsis group was reduced compared to the control group, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%